Environmental Altruistic Behavior of School Students in North Maluku, Indonesia - Lysna Lubis, Muhammad Agus Umar, Nadiroh (International Journal of Advanced Science and Technology, 2020)
Previous research studies have shown that students want to do altruistic behavior with others without reward. However, questions about how students do altruistic behavior towards the environment are rarely investigated. This study aimed to determine the relationship between spiritual intelligence, students' knowledge of ecological concepts, and locus of control with environmental altruistic behavior of high school students in South Halmahera Regency ,  North Maluku Province, Indonesia. The method used was survey with a correlational study approach involving 85 students as a research sample. There were four instruments that measure environmental altruistic behavior (rails. 907) namely spiritual intelligence (r. 377), student knowledge about ecological concepts (r.959), and locus of control (r. 971). Data were analyzed by ANOVA. The results of the study showed  that there was  positive and significant correlation between these variables, although it had been controlled by second-order correlation  but still remained significant. Therefore, it can be concluded that if environmental altruistic behavior wants to be improved, spiritual intelligence, students' knowledge of ecological concepts, and locus of control must be considered.